Correlation of Incisors Inclination and Position with Facial Profile - Ne'am F Agha; Zeina M Ahmad; Zaid B Al-Dewachi (University of Mosul, College of Dentistry, 2011)
Aims: This study aimed to assess the relationship between upper and lower incisors and soft tissue fa-cial profile. Materials and methods: The sample included forty eight Iraqi adults (22 men, 26 women) with Class I normal occlusion. Seven soft tissue parameters and six skeletal and incisal parameters were measured on lateral cephalometric radiographs. The data were analyzed using independent sample t test and Pearson correlation analysis. Results: sexual dimorphism was reported only for soft tissue convexity angle and interlabial angle. The results also showed correlation between incisor parameters and soft tissue parameters. Lower incisor inclination showed negative correlation with soft tissue pro-file angle for male and total samples. While both upper and lower incisors positions showed positive correlation with upper lip/NP angle and soft tissue pogonion/NP distance. Positive correlation was no-ticed between interincisal angle and soft tissue profile convexity angle for the total sample. Conclu-sions: upper and lower incisors are correlated to the overlying soft tissue structures. This correlation was mostly significant for the upper lip vermilion, upper lip base and tip of the nose.